2017
DOI: 10.1080/2162402x.2017.1287247
|View full text |Cite
|
Sign up to set email alerts
|

The Interleukin (IL)-1R1 pathway is a critical negative regulator of PyMT-mediated mammary tumorigenesis and pulmonary metastasis

Abstract: Breast cancer is the most common cancer in women and the second leading cause of female cancerrelated deaths worldwide. Inflammation is an established hallmark of tumorigenesis and an important determinant of tumor outcome and response to therapy. With advances in cancer immunotherapy, there is an urgent need to dissect the contribution of specific immune effectors in cancer development. Here, we genetically investigated the role of the Interleukin-1 (IL-1) receptor 1 (IL-1R1) pathway in breast cancer tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…This screen identified genes that satisfied three criteria: 1) significantly reduced the migration of ARID1A knockdown cells, 2) had little to no effect on WT cells, and 3) abrogated the migratory differences between WT and ARID1A knockdown cells (Figures 7E and 7F). Among these genes, EMILIN1, MAT1A, IL1R1, and LCN2 were previously associated with metastasis suppression (Dagenais et al, 2017; Danussi et al, 2012; Wang et al, 2013; J. Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This screen identified genes that satisfied three criteria: 1) significantly reduced the migration of ARID1A knockdown cells, 2) had little to no effect on WT cells, and 3) abrogated the migratory differences between WT and ARID1A knockdown cells (Figures 7E and 7F). Among these genes, EMILIN1, MAT1A, IL1R1, and LCN2 were previously associated with metastasis suppression (Dagenais et al, 2017; Danussi et al, 2012; Wang et al, 2013; J. Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…No known drivers were uniquely present in this primary tumour subclone. However, we did identify a nonsense variant in IL1R1, a gene which is thought to act as a tumour suppressor 30 . This subclonal cluster within the primary tumour might correspond to the lineage that originated the metastases (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…In addition to the main clonal cluster, we further identified that the two primary tumour samples harboured the same subclone represented by 37 SNVs (at CCF 0.25 95% CI 0.22-0.37 and 0.29 95% CI 0.18-0.34 for samples PD38258u and PD38258v, respectively), which were fixed and became truncal across the metastases. No known drivers were uniquely present in this primary tumour subclone, however, we did identify a nonsense variant in IL1R1, a gene which is thought to act as a tumour suppressor 27 . Taken together, this indicates that the long trunk of the phylogenetic tree originated from this subclonal cluster within the primary tumour, and that the non-truncal metastatic clones arose de novo during metastatic dissemination ( Fig.…”
Section: Reconstructing the Phylogenetic Tree Based On The Non-truncamentioning
confidence: 70%